2020
DOI: 10.1101/2020.06.08.139600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced production of taxadiene inSaccharomyces cerevisiae

Abstract: Metabolic Engineering 23Highlights 27• Maximum taxadiene titre of 129 ± 15 mg/L in Saccharomyces cerevisiae at 20 °C 28• Integrating fusion protein tagged-taxadiene synthase improved taxadiene titre. 29• Consistent taxadiene titres were achieved at the micro-and mini-bioreactor scales. 30 Abstract 31Cost-effective production of the highly effective anti-cancer drug, paclitaxel (Taxol®), remains 32 limited despite growing global demands. Low yields of the critical taxadiene precursor remains a 33 key bottleneck… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The LRS5 strain produced a maximum taxadiene titer of 137 ± 5 g/L when grown in 4% galactose (100:0) medium. This represented 1.06 and 2.5-fold improvements in taxadiene titer to 137 ± 5m g/L compared with the highest literature titers for the strain at 20 and 30°C (Nowrouzi et al, 2020). Although TASY activity has been found to be enhanced at reduced temperature (Nowrouzi et al, 2020), preliminary studies (results not shown) using LRS6 revealed that CYP725A4 activity was dramatically reduced at 20°C compared with 30°C.…”
Section: Taxane Product Profiles Using Microscale Bioreactorsmentioning
confidence: 80%
See 4 more Smart Citations
“…The LRS5 strain produced a maximum taxadiene titer of 137 ± 5 g/L when grown in 4% galactose (100:0) medium. This represented 1.06 and 2.5-fold improvements in taxadiene titer to 137 ± 5m g/L compared with the highest literature titers for the strain at 20 and 30°C (Nowrouzi et al, 2020). Although TASY activity has been found to be enhanced at reduced temperature (Nowrouzi et al, 2020), preliminary studies (results not shown) using LRS6 revealed that CYP725A4 activity was dramatically reduced at 20°C compared with 30°C.…”
Section: Taxane Product Profiles Using Microscale Bioreactorsmentioning
confidence: 80%
“…This represented 1.06 and 2.5-fold improvements in taxadiene titer to 137 ± 5m g/L compared with the highest literature titers for the strain at 20 and 30°C (Nowrouzi et al, 2020). Although TASY activity has been found to be enhanced at reduced temperature (Nowrouzi et al, 2020), preliminary studies (results not shown) using LRS6 revealed that CYP725A4 activity was dramatically reduced at 20°C compared with 30°C. In addition, both growth rate in S. cerevisiae (Nowrouzi et al, 2020) and CYP725A4 activity in E. coli (Biggs et al, 2016) have been found to be reduced at a lower temperature.…”
Section: Taxane Product Profiles Using Microscale Bioreactorsmentioning
confidence: 80%
See 3 more Smart Citations